Efficiency Performance of General Insurance Companies in Malaysia - Qian, Long Kweh; Noor Azlinna, Azizan (Academic Research Online Publisher, 2015)
A two-stage approach in data envelopment analysis (2S-DEA) methodology is used towards decomposing a typical two-stage operation process of general insurance companies, which is conducted in a single operation involving intermediate. Specifically, we evaluate the managerial efficiency and profitability efficiency of Malaysia-incorporated companies involving in general insurance business for the period 2008-2011, by using the additive efficiency decomposition approach in 2S-DEA of Chen, Cook, Li, and Zhu(2009). We find that the sample firms have to first improve their managerial efficiency, and then proceed to improve their profitability efficiency.